Elections in Oxford County, 1837-1875 : a case study of democracy in Canada West and early Ontario - Emery, George Neil, 1941- (University of Toronto Press, 2012)
Elections in Oxford County, 1837-75 breaks new ground with its detailed treatment of the county's voice-vote method of election, which ended with the adoption of the secret ballot in 1874.